KENISCAYAAN PENGGUNAAN ANALISIS GENDER DALAM STUDI AL-AHWĀL ASY-SYAKHSIYYAH - Bani Syarif Maula (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2016)
Al-Ah}wāl asy-Syakhs}iyyah is one of the Islamic studies that seems containing many legal rules opposed to the concept of modern society. Therefore, the study of al-Ah}wāl asy-Syakhs}iyyah on the perspective of gender analysis is needed to answer the problems of Muslim society in facing democratization in which discourses on human rights and gender equality become its main issues. One of the efforts to reform the rules of al-Ah}wāl asy-Syakhs}iyyah is by understanding the asy-Sya>t}ibi>'s concept on ibadah and muamalah. According asy-Sya>t}ibi>, ibadah is pure God's rules, whose purpose can not be captured by the power of human reasoning, so that the provisions of ibadah have to be practiced as is stated in the Quran textually. In contrast, muamalat is rules on human relations where human become center, its purpose can be captured by reasoning, and muamalat provisons on the Quran should be understood by their perceived meaning, not their textual rules. In addition, an understanding of Islamic law should depart from the basic assumption that muamalah rules were revealed from the result of human interaction with their social conditions.